2008
DOI: 10.1128/aac.01216-07
|View full text |Cite
|
Sign up to set email alerts
|

Complete DNA Sequence and Analysis of the Transferable Multiple-Drug Resistance Plasmids (R Plasmids) from Photobacterium damselae subsp. piscicida Isolates Collected in Japan and the United States

Abstract: Photobacterium damselae subsp. piscicida is a bacterial fish pathogen that causes a disease known as pasteurellosis. Two transferable multiple-drug resistance (R) plasmids, pP99-018 (carrying resistance to kanamycin, chloramphenicol, tetracycline, and sulfonamide) and pP91278 (carrying resistance to tetracycline, trimethoprim, and sulfonamide), isolated from P. damselae subsp. piscicida strains from Japan (P99-018) and the United States (P91278), respectively, were completely sequenced and analyzed, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 17 publications
4
56
0
1
Order By: Relevance
“…Nevertheless, the nucleotide sequences of the regions shared with the bla CMY-2 -bearing IncA/C plasmids were identical, suggesting that the bla CMY-2 -bearing plasmids could be the result of the insertion of DNA modules into this smaller precursor plasmid Wiesner et al, 2011). The general agreement from the analysis of the genetic structure of the IncA/C group,is that plasmid evolution progresses faster through the insertion/deletion of DNA stretches rather than by point mutations (Welch et al, 2007;Kim et al, 2008;Fricke et al, 2009;Call et al, 2010;Wiesner et al, 2011).…”
Section: Antimicrobial Resistance and Virulence Plasmidssupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, the nucleotide sequences of the regions shared with the bla CMY-2 -bearing IncA/C plasmids were identical, suggesting that the bla CMY-2 -bearing plasmids could be the result of the insertion of DNA modules into this smaller precursor plasmid Wiesner et al, 2011). The general agreement from the analysis of the genetic structure of the IncA/C group,is that plasmid evolution progresses faster through the insertion/deletion of DNA stretches rather than by point mutations (Welch et al, 2007;Kim et al, 2008;Fricke et al, 2009;Call et al, 2010;Wiesner et al, 2011).…”
Section: Antimicrobial Resistance and Virulence Plasmidssupporting
confidence: 73%
“…They have attracted the attention of the research community due to their ability to acquire antimicrobial resistance traits and to mobilize across geographical and taxonomical borders (Fricke et al, 2009). Recent comparative studies have addressed the evolutionary relationships among the IncA/C plasmids from Salmonella enterica, Escherichia coli, Yersinia pestis, Yersinia ruckeri, Vibrio cholera, Photobacterium damselae and Aeromonas salmonicida (Welch et al, 2007;Kim et al, 2008;McIntosh et al, 2008;Pan et al, 2008;Fricke et al, 2009;Call et al, 2010). The genomic comparison of seven IncA/C plasmids showed that these plasmids share a common backbone, including the origin of replication and a conjugative plasmid transfer system (Welch et al, 2007;Fricke et al, 2009).…”
Section: Antimicrobial Resistance and Virulence Plasmidsmentioning
confidence: 99%
“…PCR with a set of primers TCr3-F1 5 -AGCCTGACCAATCTGAC-3 and TCr3-R5 5 -GTGAAGAAGTGGCAGATC-3 described in Fig.2, and TA3 as a template DNA indicated the presence of adhC and ORF2, and IS26-Right in opposite orientation to the IS26-Left Fig.2A . The flanking region by IS26-Left and -Right was identical to the structure found in Photobacterium damselae Kim et al, 2008;Kim and Aoki, 1994 except for the ISRSB101. The inserted ISRSB101 was 100% identical to that of plasmid pFBOAT6 of Aeromonas punctata Rhodes et al, 2004 , and was bordered by direct repeats of 9 nucleotide 5 -TGTTGCAAA-3 originating from IS26-Inner.…”
Section: Is26-innermentioning
confidence: 55%
“…TA3 pTCKM3 . Solid bars indicate the regions which exhibit homology to the reported sequences; pP99-018 from Photobacterium damselae Kim et al, 2008;Kim and Aoki, 1994 , Salmonella serovar Ordnez Allard et al, 1993 , and pFBAOT6 from Aeromonas punctata Rhodes et al, 2004 . B The structure found in Salmonella sp.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation